2021
DOI: 10.1093/ofid/ofab104
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing for Pathogen Detection and Transcriptomic Analysis in Pediatric Central Nervous System Infections

Abstract: Background Pediatric central nervous system (CNS) infections are potentially life-threatening and may incur significant morbidity. Identifying a pathogen is important, both in terms of guiding therapeutic management, but also in characterizing prognosis. Usual care testing by culture and PCR is often unable to identify a pathogen. We examined the systematic application of metagenomic next-generation sequencing (mNGS) for detecting organisms and transcriptomic analysis of cerebrospinal fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In-depth etiological analysis showed that the distribution of pathogenic bacteria and viruses detected was basically consistent with the epidemiology of pathogens in pediatric CNS infections ( 45 ). The development of the human immune system is a continuous process, potentially gaining peak function during adolescence ( 46 ), which makes young children at greater risk of developing infections than older children and adults and makes them more vulnerable to disseminated infections ( 47 , 48 ), including CNS infections.…”
Section: Discussionmentioning
confidence: 61%
“…In-depth etiological analysis showed that the distribution of pathogenic bacteria and viruses detected was basically consistent with the epidemiology of pathogens in pediatric CNS infections ( 45 ). The development of the human immune system is a continuous process, potentially gaining peak function during adolescence ( 46 ), which makes young children at greater risk of developing infections than older children and adults and makes them more vulnerable to disseminated infections ( 47 , 48 ), including CNS infections.…”
Section: Discussionmentioning
confidence: 61%
“…Protein–protein interaction enrichment analysis also identified this GO term, suggesting that it is part of the host response to viral infection. Therefore, transcriptome analysis supports the results of metagenomic NGS and elucidates the host immune response [ 54 ]. These results may be useful for understanding the pathophysiology of various pediatric CNSIs.…”
Section: Discussionmentioning
confidence: 90%
“…Of which, four studies were retrospective ( 15 , 16 , 18 , 20 ) and eight were prospective ( 9 , 17 , 19 , 21 25 ). Studies were conducted in the following countries: China ( 9 , 17 , 22 , 23 ), the United States ( 16 , 18 21 , 24 ), Canada ( 15 ), and the unknown ( 25 ). A total of 1,249 participants were analyzed in the 12 studies.…”
Section: Resultsmentioning
confidence: 99%